MicroRNA expression and protein acetylation pattern in respiratory and limb muscles of Parp-1−/− and Parp-2−/− mice with lung cancer cachexia - Chacon-Cabrera, Alba; Fermoselle, Clara; Salmela, Ida; Yelamos, Jose; Barreiro, Esther (Biochimica et biophysica acta, 2015)
Current treatment options for cachexia, which impairs disease prognosis, are limited. Muscle-enriched microRNAs and protein acetylation are involved in muscle wasting including lung cancer (LC) cachexia. Poly(ADP-ribose) polymerases (PARP) are involved in muscle metabolism. We hypothesized that muscle-enriched microRNA, protein hyperacetylation, and expression levels of myogenic transcription factors (MTFs) and downstream targets, muscle loss and function improve in LC cachectic Parp-1−/− and Parp-2−/− mice. Body and muscle weights, grip strength, muscle phenotype, muscle-enriched microRNAs (miR-1, -133, -206, and -486), protein acetylation, acetylated levels of FoxO1, FoxO3, and PGC-1α, histone deacetylases (HDACs) including SIRT1, MTFs, and downstream targets (α-actin, PGC-1α, and creatine kinase) were evaluated in diaphragm and gastrocnemius of LC (LP07 adenocarcinoma) wild type (WT), Parp-1−/− and Parp-2−/− mice. Compared to WT cachectic animals, in both respiratory and limb muscles of Parp-1−/− and Parp-2−/− cachectic mice: downregulation of muscle-specific microRNAs was counterbalanced especially in gastrocnemius of Parp-1−/− mice; increased protein acetylation was attenuated (improvement in HDAC3, SIRT-1, and acetylated FoxO3 levels in both muscles, acetylated FoxO1 levels in the diaphragm); reduced MTFs and creatine kinase levels were mitigated; body and muscle weights, strength, and muscle fiber sizes improved, while tumor weight and growth decreased. These molecular findings may explain the improvements seen in body and muscle weights, limb muscle force and fiber sizes in both Parp-1−/− and Parp-2−/− cachectic mice. PARP-1 and -2 play a role in cancer-induced cachexia, thus selective pharmacological inhibition of PARP-1 and -2 may be of interest in clinical settings. [Display omitted] •Current treatment options for cachexia are limited•Muscle-enriched microRNAs and protein acetylation contribute to muscle wasting•Poly(ADP-ribose) polymerases (PARP) may play a role in muscle metabolism•MicroRNA and protein acetylation levels improved in diaphragm and gastrocnemius in Parp-1–/– and Parp-2–/– lung cancer cachectic mice•PARP-1 and -2 are involved in cancer-induced cachexia in respiratory and limb muscles